Case-report: A rare cause of intestinal obstruction in late pregnancy. (March 2021) - Dholoo, Farzan; Shabana, Amanda; See, Abbas; Hameed, Waseem
Highlights: Caecal volvulus represents a rare and often life-threatening cause of intestinal obstruction, with associated high mortality rates. Diagnosis and early intervention remain a challenge, as patients may only present with vague nonspecific symptoms. More classical symptoms of volvulus eventually occur, usually secondary to obstruction or ischaemia. Early diagnosis and intervention are of paramount importance. We advise clinicians to remember this diagnosis, as a potential cause of abdominal pain and obstruction; especially in those with risk factors. Abstract: Introduction: Caecal volvulus represents a rare and often life-threatening cause of intestinal obstruction. Diagnosis and management of caecal volvulus remains a clinical challenge, since those presenting with symptoms can have vague nonspecific presentations. Symptoms eventually occur, usually secondary to obstruction or ischaemia. This case report will discuss the presentation, investigation and management options available. Presentation: A 31-year-old multigravida, at 38 weeks and 6 days gestation; presented to hospital with a 2-day history of diffuse abdominal pain and distension. Initial examination was unremarkable aside from mild epigastric tenderness. Raised inflammatory markers and concerns for foetal health resulted in an emergency caesarean section. Symptoms however worsened and the patient underwent colonoscopy and computerised tomography (CT) of the abdomen and pelvis with contrast; showing caecal volvulus. The patient was taken to the operating theatres for an emergency right hemicolectomy with formation of end ileostomy. Intra-operatively, areas of necrosis were noted within the caecum suggestive of impending perforation. The patient recovered well post reversal of end ileostomy, with no complications to date. Discussion: Caecal volvulus represents a rare, but potentially fatal cause of intestinal obstruction and ischaemia. High mortality rates are attributed to delayed diagnosis and treatment. Patients may initially present with vague symptoms, which rapidly progress with the development of ischaemia. Multiple management modalities exist. Central to prognosis is early diagnosis. Conclusion: Early diagnosis and intervention are paramount. Imaging via abdominal x-rays and CT are of particular importance. Surgical management is widely reported as the mainstay of treatment. We advise clinicians to remember this rare diagnosis, as a potential cause of abdominal pain and intestinal obstruction; especially in those with predisposing risk factors.